AR in science education – an AR based teaching‐learning scenario in the field of teacher education - Krug, Manuel; Czok, Valerie; Müller, Sascha; Weitzel, Holger; Huwer, Johannes; Kruse, Stefan; Müller, Wolfgang (Chemkon, 2022)
Mit Augmented Reality angereicherte Lehr‐Lernsettings gewinnen sowohl im Schulfach Chemie als auch in anderen naturwissenschaftlichen Fächern immer mehr an Bedeutung. So erwähnen viele Publikationen die positiven Effekte solcher digital angereicherter Lehr‐Lernprozesse, geben jedoch nur selten darüber Auskunft, welche Eigenschaften der erweiterten Realität hierfür verantwortlich sind. Dieser Beitrag stellt ein Bewertungsraster vor, mit dessen Hilfe es ermöglicht wird, mit Augmented Reality angereicherte Lehr‐Lernsettings in Bezug auf medien‐ und fachdidaktische Aspekte hin zu bewerten. Des Weiteren wird eine exemplarische Darstellung der Umsetzung eines digital angereicherten Lehr‐Lernsettings im Kontext der Nachhaltigkeitsbildung vorgestellt. Teaching‐learning settings enriched with augmented reality are becoming increasingly important both in the school subject of chemistry and in other natural science subjects. Thus, many publications mention the positive effects of such digitally enriched teaching‐learning processes, but rarely provide information about which characteristics of augmented reality are responsible for this. This paper presents an evaluation grid which allows to evaluate teaching‐learning settings enriched with augmented reality with a focus on media and subject didactical aspects. Furthermore, an exemplary presentation of the implementation of a digitally enriched teaching‐learning setting in the context of sustainability education is presented.